Pengaruh Moderasi Dalam Kerukunan Beragama - Siti Afifah; Rosa Kamelia Sari; Kiki Verina; Meilisa Sajadah (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Moderation in religion is an important concept in the context of religious harmony. This study aims to explore the influence of moderation in religion on religious harmony. The methods used were surveys and inter views with respondents representing various religions in Indonesia. The results showed that moderation in religion has a positive influence on religious harmony. This is reflected in an attitude of tolerance, respect for diversity, and stronger national commitment among individuals who practice religious moderation. The implication of this research is the importance of promoting moderation in religion as a foundation to streng then religious harmony in Indonesia.